Deterioration Detection of Heavy-Duty Anticorrosion Coating Using Near-Infrared Hyperspectral Imaging - Shinsuke Haruna; Yuki Ogawa; Takumi Sakata; Daiki Shiozawa; Takahide Sakagami; Yoshiteru Yokoi; Takeshi Sugiyama (Engineering Proceedings, 2023)
Steel bridges are usually painted with anticorrosion coatings. Early detection of the deterioration of the top coat is important for preventive maintenance. To detect the exposed area of the middle coat due to the deterioration of the top coat, this study introduces near-infrared hyperspectral imaging. The exposed area of the middle coat can be detected by finding the wavelengths with large differences in the spectral characteristics of both coats. Moreover, principal component analysis was applied to hyperspectral data. Principal component analysis can accurately detect the exposed area of middle coats based on differences in spectral characteristics in the near-infrared region of the coating.